2022
DOI: 10.1111/iwj.13839
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of moist dressings in wound healing after surgical suturing: A Bayesian network meta‐analysis of randomised controlled trials

Abstract: The moist healing theory proves that a moderately moist and airtight environment is conducive to wound healing. However, different moist dressings have different functions. We aim to evaluate the effects of moist dressings on wound healing after surgical suturing and identify superior moist dressings. Randomised controlled trials investigating the application of moist dressings were retrieved from electronic databases, including PubMed, EMBASE, Web of Science, and the Cochrane Library. Wound healing, surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Worldwide, Surgical site infections are the most commonest infections presenting within a month [1][2][3][4][5]. Our study too, has also found the increased similar duration of presentation of postoperative infections [12,1].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Worldwide, Surgical site infections are the most commonest infections presenting within a month [1][2][3][4][5]. Our study too, has also found the increased similar duration of presentation of postoperative infections [12,1].…”
Section: Discussionsupporting
confidence: 74%
“…Worldwide, Surgical site infections are the most commonest infections presenting within a month [1][2][3][4][5]. Our study too, has also found the increased similar duration of presentation of postoperative infections [12,1]. nowadays the emerging cause behind serious infections is the development of drug resistance brought on by improper usage and administration of antibiotics.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This is because the molecular structure of CS contains hydrophilic groups such as amino and hydroxyl groups, which enhance the hygroscopic properties of the fiber membrane [ 45 , 46 ]. Studies have shown that the high swelling ratio of the PN@8 wt%Ag-2 h electrospun fiber membrane could provide a suitable moist environment for the wound, thus speeding up the wound healing [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%